Cognitive Behavior Therapy for Anxiety in People With Dementia: A Clinician Guideline for a Person-Centered Approach. (May 2015) - Charlesworth, Georgina; Sadek, Susan; Schepers, Astrid; Spector, Aimee
This article describes a 10-session cognitive-behavioral therapy (CBT) used in a randomized controlled trial with people with anxiety and mild-to-moderate dementia. The aim of the therapy is to reduce symptoms of anxiety by increasing a sense of safety and self-efficacy. The therapy is characterized by a person-centered approach to CBT, using individual tailoring to accommodate for cognitive deficits and other challenges. Three phases of therapy are described: (a) socialization to model (including overcoming barriers to participation), goal setting, and formulation; (b) application of cognitive and behavioral change techniques to address unhelpful autonomic reactions, "strategic" reactions, "rules for living, " and interpersonal aspects; and (c) consolidation and ending in the context of chronic, deteriorating illness. The approach prioritizes direct work with the person with dementia, with the involvement of a "supportive other" where available and when necessary. The protocol is designed for use by therapists with prior experience in CBT.